Characterization of wafers by V(Z) curve technique of scanning acoustic microscopy - Loh, Edwin Jin Wee. (2009)
The report presents the work performed on the evaluation of Young’s Modulus using the V(z) curve technique. The background of V(z) curve technique in determining the material properties non-destructively is introduced. In order for readers to understand the procedures undertaken for the project, a chapter for the necessary knowledge has been allocated.